2014
DOI: 10.1002/gps.4213
|View full text |Cite
|
Sign up to set email alerts
|

Asenapine in the treatment of older adults with bipolar disorder

Abstract: Objective In spite of growing numbers of elderly there are few treatment studies on late-life bipolar disorder (BD). This was a 12-week prospective, open-label trial to assess efficacy and tolerability of adjunct asenapine in non-demented elderly (≥60 years) with sub-optimal previous response to BD treatments. Methods Asenapine was initiated at 5 mg/day and titrated as tolerated. Effects on global psychopathology were measured with Clinical Global Impression, Bipolar version (CGI-BP) and the Brief Psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Quetiapine (level 2)655 can be considered as second‐line. Asenapine (level 4),656, 657 aripiprazole (level 4),658 risperidone (level 4),659 or carbamazepine (level 4)654 may be applied as third‐line treatments. For treatment‐resistant episodes, clozapine (level 4)660 and ECT (level 4)654 should also be considered.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Quetiapine (level 2)655 can be considered as second‐line. Asenapine (level 4),656, 657 aripiprazole (level 4),658 risperidone (level 4),659 or carbamazepine (level 4)654 may be applied as third‐line treatments. For treatment‐resistant episodes, clozapine (level 4)660 and ECT (level 4)654 should also be considered.…”
Section: Specific Populationsmentioning
confidence: 99%
“…We found 53 articles on OABD in the last 6 years . Of those, 50 (94%) papers examined clinical samples ranging from 10 to 315 subjects (total of 3302 subjects, mean ± standard deviation (SD) 62.3 ± 51.5 subjects/paper, median 53 subjects/paper).…”
Section: Resultsmentioning
confidence: 99%
“…All studies ( n = 53) reported age and gender. Levels of education were the next most often reported ( n = 34 studies, 64%), followed by ethnicity ( n = 23, 43%) and marital status ( n = 17, 32%) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…asenapine is registered for the treatment of acute and long-term schizophrenia in adults and for the acute treatment of manic or mixed episodes associated with BDI [8]. This was based on the results of several randomized controlled studies supporting its efficacy and good tolerability in both short-and long-term use in schizophrenic and BD patients in monotherapy [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and in BDmixed episode [27][28][29]. The recommended dose of asenapine in monotherapy is 10 mg twice a day that can be reduced to 5 mg twice a day depending on the patient's response.…”
Section: Introductionmentioning
confidence: 99%